Cultural differences in the production of emotional facial expressions: a review - Gallant, Adèle; Mazerolle, Marie-Pier; Pelot, Annalie; Roy-Charland, Annie (Frontiers in Psychology, 2026)
Whereas cross-cultural differences in recognition of emotional facial expressions are widely established, less information exists regarding differences in their production. The current systematic review was conducted to summarize and clarify the role of culture in the production of emotional facial expressions. Following a two-step process, 21 peer-reviewed articles were included within the current review, from which four categories were generated exploring findings from child/infant and adult studies separately: (1) production of spontaneous expressions, (2) production of posed expressions, (3) comparison of spontaneous and posed expressions, and (4) others. Whereas the production of emotional facial expressions is shown to be largely universal, culturally variable nuances exist but vary according to spontaneous versus posed expressions.